Mycobacterium tuberculosis KasA as a drug target: Structure-based inhibitor design - Rudraraju, Reshma S.; Daher, Samer S.; Gallardo-Macias, Ricardo; Wang, Xin; Neiditch, Matthew B.; Freundlich, Joel S. (Frontiers in Cellular and Infection Microbiology, 2022)
Recent studies have reported the β-ketoacyl-acyl carrier protein KasA as a druggable target for Mycobacterium tuberculosis. This review summarizes the current status of major classes of KasA inhibitors with an emphasis on significant contributions from structure-based design methods leveraging X-ray crystal structures of KasA alone and in complex with inhibitors. The issues addressed within each inhibitor class are discussed while detailing the characterized interactions with KasA and structure-activity relationships. A critical analysis of these findings should lay the foundation for new KasA inhibitors to study the basic biology of M. tuberculosis and to form the basis of new antitubercular molecules of clinical significance with activity against drug-sensitive and drug-resistant infections.